(untitled) (Journal of Medical Sciences, 2021)
A total of 90 isolates were obtained from two different sites (Al- Mahdia and Al-Jadeed) of Sebha city. Out of this number twenty eight (30%) isolates showed contamination of gastrointestinal protozoan parasites, namely Entamoeba histolytica/Entamoeba dispar (5.55%), Entamoeba coli (8.88%), Blastocystis hominis (15.55%) on external surface (body) of house flies. Only one isolate from Al- Mahdia locality showed Hymenolepis nana (1.11%) infestation to the house flies. In Al-Jadeed area, H.nana was not recorded in the isolates. Findings of this study indicate a relatively high infectivity rate in the disease vectors. House flies appeared to be a potential mechanical vector of intestinal protozoa in Sebha city and might be in other parts of Libya. This is the first study in Libya, which will provide knowledge on contamination of intestinal parasitic recovered from different external body parts of house flies.